Twenty years operating of Flerov nuclear reaction laboratory microtron MT-17 in Vietnam - Theip, Tran Duc; Van Do, Nguyen; Khac Thi, Nguyen; Manh Sat, Nguyen; Thi An, Troung; Dinh Phu, Tran (Scientific transaction of the National University of Mongolia. Physics, 2022)
Mictrorons are accelerators of electrons and simultaneous sources of bremsstrahlung photon flux and fission neutrons. In 1982, a microtron of seventeen trajectories Microtron MT - 17 of FLNR put into operation at the National Institute of Physics of Vietnam. Thouf very modest, raicrotrons are very useful for developing countries such i Vietnam in both fundamental and applied physics research During the recei twenty years by using the above mentioned Microtron MT - 17 at microtrons from other institutes we have carried out different investigation In this report we present some results obtained in the studies of photonucle. reactions and photon activation analysis in the giant dipole resonance region